2007
DOI: 10.1016/j.molimm.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of recombinant human Fc:OX40L fusion protein linked via a coiled-coil trimerization domain

Abstract: OX40 (CD134) is a potent costimulatory molecule found on the surface of activated CD4 + and CD8 + T cells. Immunotherapy with OX40 agonists administered in vivo has demonstrated efficacy in several murine tumor models. A phase I clinical trial is currently underway in patients with advanced cancer using a mouse anti-CD134 monoclonal antibody. Therapy with this antibody will likely be limited to one cycle because patients develop neutralizing human anti-mouse antibody (HAMA). Therefore, we developed a humanized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…The anti-tumor activity of anti-mouse CD40 in these studies is lost upon introduction of the D265A mutation into its Fc domain [13], which results in an antibody with no measurable FcγR binding [6]. It has also been shown that the in vitro activity of antibodies directed against other TNFRs in human cells, such as OX40, GITR, CD137 and CD27, requires, or is greatly enhanced by FcγR engagement or immobilisation [25,26]. While the evidence suggests that a requirement for cross linking is a common property of antibodies targeting TNFRs receptors, there are some exceptions.…”
Section: The Canonical Role Of Fcγrs In Immunomodulatory Antibodiesmentioning
confidence: 93%
“…The anti-tumor activity of anti-mouse CD40 in these studies is lost upon introduction of the D265A mutation into its Fc domain [13], which results in an antibody with no measurable FcγR binding [6]. It has also been shown that the in vitro activity of antibodies directed against other TNFRs in human cells, such as OX40, GITR, CD137 and CD27, requires, or is greatly enhanced by FcγR engagement or immobilisation [25,26]. While the evidence suggests that a requirement for cross linking is a common property of antibodies targeting TNFRs receptors, there are some exceptions.…”
Section: The Canonical Role Of Fcγrs In Immunomodulatory Antibodiesmentioning
confidence: 93%
“…Such problems have been reported in the development of agonistic OX40L fusion protein [145]. However, such antibodies were not generated in a trial of OX40L blockade [142].…”
Section: Box 1: Rationale For Targeting Ox40-ox40l Interactions In Aumentioning
confidence: 99%
“…These include cancer therapeutics that have been tested in clinical trials, such as the TNF superfamily member CD40 ligand (6 -8), as well as therapeutics that have been tested preclinically, such as OX40 ligand (9) and TRAIL (10). Experimental protein vaccines, some, which are considered for clinical trials, also exploit IZ and/or Fd and include the spike proteins of human immunodeficiency virus (HIV-1) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), respiratory syncytial virus (21,22), and influenza virus (4,(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%